Molecular Discrimination between Organic and Conventional Liquid Milk Products in Thailand Using ¹H-NMR Metabolomics Approach - T. Phuenpong; M. Kongboonkird; K. Duangmal; W. Lerdvorasap; M. Suksawwawimon; W. Mekboonsonglarp; J. Nuamchit; N. Chantaprasarn; S. Settachaimongkon (Tropical Animal Science Journal, 2021)
The aims of this study were to characterize and compare non-volatile polar metabolite profiles of organic and conventional liquid milk products using a non-targeted proton nuclear magnetic resonance (1H-NMR) metabolomics approach. Pasteurized plain-liquid milk products from 10 different brands available in Thai marketplace were analyzed for their major chemical compositions and 1H-NMR derived metabolome data. Results demonstrated no specific trend for differentiation between organic and conventional milk samples based on their pH, fat, protein, lactose, and milk solid-not-fat compositions. A total of 45 non-volatile polar metabolites in milk samples were identified by 1H-NMR technique. The chemometric analysis allowed discrimination between organic and conventional milk samples based on their 1H-NMR metabolite profiles. Changes in the relative concentration of formate, betaine, dimethyl sulfone, 2-oxoglutarate, creatine, pyruvate, butyrate, proline, acetoacetate, alanine, glycerophosphocholine, carnitine, and hippurate were statistically identified as potential biomarkers accountable for the discrimination between organic and conventional milk samples in this study. Variations of these compounds might be the reflections of animal diets, rumen fermentation, and physiological adaptation of the cows raised in organic dairy farming systems. Our findings provide new insights and support the effectiveness of using a non-targeted 1H-NMR combined with chemometrics to investigate the molecular authenticity of organic food products.